Advancing ecological validity and clinical utility in virtual reality-based continuous performance test: exploring the effects of task difficulty and environmental distractors - Oh, Hyang-Kyeong; Cho, Yoon Jae; Kim, Jae-Jin; Shin, Bokyoung; Kim, Soo-Jeong; Park, Soobin; Seok, Jeong-Ho; Kim, Soyeon; Kim, Eunjoo (Frontiers in Psychiatry, 2024)
Introduction Researchers have highlighted concerns regarding the limited diagnostic utility and ecological validity of the Continuous Performance Test (CPT). Recent advancements in VR-based CPTs have attempted to address these concerns by simulating real-life scenarios and enhancing attention deficit hyperactivity disorder (ADHD) diagnosis; however, certain areas require improvement for obtaining reliable data from both healthy individuals and those with ADHD. To tackle these issues, we developed an enhanced VR-based CPT program featuring four distinct difficulty levels, advancing toward home-based assessment. Method Our feasibility study involved subjects without ADHD to establish a normative profile for VR-based CPT before extending it to ADHD assessment. Our sample included 20 Korean adults. They received a VR device with the VR-based CPT program installed and were asked to perform 1-2 blocks per day at home. Participants were instructed to complete 12 blocks over the subsequent 2 weeks. Psychological assessments and electroencephalograms (EEGs) were administered before and after the program. Post-study usability measures were also collected. Result Higher commission errors were notably evident in the “very high” difficulty level which featured complex stimuli and increased distraction. A notable correlation emerged between the overall distraction level and CPT accuracy, along with a significant link between intensity scores and commission errors. No significant differences were found in psychological assessment and there were no significant changes in the Theta-Beta Ratio (TBR) index before and after the program. The usability of our program was fair. Discussion The study reveals that the newly designed VR-CPT program, simulating diverse real-life environments and offering varying task difficulty levels, proved acceptable and feasible. The key point of our study was that the adjustment and segmentation of difficulty levels in the VR-based CPT were achieved, and that this effort was validated by examining the impact of different levels of difficulty on CPT measures. Implementing this experimental setup in a home-based environment increased ecological validity, as well as clinical utility. Limitations and suggested directions for further investigation are described in detail.